PROTOTYPE ALAT PEMANTAUAN DAN PENGENDALIAN SUHU RUANGAN SARANG WALET BERBASIS NODEMCU - Husdi Husdi; Sayoga Mohamad Galih (STMIK Catur Sakti Kendari, 2023)
Swallow is a type of bird widely cultivated to produce nests. In general, swallows like places with certain temperatures as nesting habitats. Stable temperature and humidity conditions can help produce high-quality swallow nests for a better and higher price. The perfect shape and color of the nest are affected by an ideal temperature of 26-29ºC and humidity of 80-90%. The unstable temperature and humidity will reduce the quality of the swallow's nest. The stability of temperature and humidity of the room greatly affects the quality of the swallow's nest. The prototype of monitoring and controlling the temperature of swallow nests is designed to make it easier for farmers to control it regularly. The results of this study are expected to make it easier for farmers not to waste too much time taking care of the swallow's house